Evaluation of Effectiveness of Sinus Surgery in Chronic Rhinosinusitis Patients using Sinonasal Outcome Index-22, modified Lund Mackay Score and Rhinosinusitis Disability Index - Pokharel, Apar; Mayya, P Jaya; Bhandari, Chhanya; Sharma, Bibek (Nepal Medical College Journal, 2024)
Functional endoscopic sinus surgery (FESS) is done in patients with chronic rhinosinusitis (CRS) not responding to medical therapy. This study aims to evaluate the subjective, objective and overall quality of life improvement in CRS patients following FESS surgery. Sinonasal outcome index-22, modified Lund-Mackay score and Rhinosinusitis Disability Index were used to evaluate subjective, objective and overall quality of life in patients with CRS. The questionnaires were asked before the surgery and three months after surgery. A total of 110 patients were enrolled in the study. All three types of evaluation showed improvement following FESS surgery. FESS in CRS patients refractory to medical management caused significant improvement in symptom intensity, endoscopic score and overall quality of life.